DIPLOMASI KEBUDAYAAN INDONESIA MELALUI BATIK DI AMERIKA SERIKAT DALAM PERSPEKTIF NEOREALIS - Rayya Adila Sakinah, (2020)
The study discusses The Indonesian Culture Diplomacy Through the Batik in America in Neorealist Perspective During President Susilo Bambang Yudhoyono's second periods Leadership. During the SBY's second periods leaderships, Indonesia' got a cultural threats in the form of Batik's claims from Malaysia. The issues of culture claims made Indonesian do the bandwagoning strategy by do the Cultural Diplomacy with the United States of America to optimize their Soft-Power. Just like what's the neorealist perspective said when a a country feel threatened so they will do the self help. The diplomatic effort is carried out with the process of Informing, Understanding, and Influencing Batik's cultures in order to gain and attract the masses of both U.S people and government. These study uses the theory of neorealist which consist the concept of soft-power, theory of diplomacy, and cultural diplomacy.